2003
DOI: 10.1104/pp.103.026518
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Cadmium with Glutathione and Photosynthesis in Developing Leaves and Chloroplasts of Phragmites australis (Cav.) Trin. ex Steudel

Abstract: We investigated how the presence of cadmium (Cd) at the emergence of Phragmites australis Trin. (Cav.) ex Steudel plants from rhizomes interacted with leaf and chloroplast physiological and biochemical processes. About 8.5 nmol Cd mg Ϫ1 chlorophyll was found in leaves, and 0.83 nmol Cd mg Ϫ1 chlorophyll was found in chloroplasts of plants treated with 50 m Cd. As a result, a 30% loss of chlorophyll was measured concomitantly with a comparable percentage reduction in light-saturated photosynthesis. Rubisco cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
129
5
15

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(172 citation statements)
references
References 51 publications
18
129
5
15
Order By: Relevance
“…of Salvinia has also been correlated with a decrease in photosynthetic pigments (Nichols et al, 2000;AlHamdani and Blair, 2004). Similar responses of decline in Rubisco activity have also been reported previously for a few aquatic species (Pietrini et al, 2003).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…of Salvinia has also been correlated with a decrease in photosynthetic pigments (Nichols et al, 2000;AlHamdani and Blair, 2004). Similar responses of decline in Rubisco activity have also been reported previously for a few aquatic species (Pietrini et al, 2003).…”
supporting
confidence: 66%
“…In this context, the increase in NADPH/NADP + ratio of Cr-exposed plants could be the consequence of either reduced utilization of NADPH resulting from a decline in Rubisco activity (thus preventing oxidation of stroma) or enhanced synthesis resulting from cyclic electron flow around PS I to meet the additional requirements of reducing equivalents during CO 2 fixation (Backhausen et al, 2000). Heavy metalinduced increases in NADPH levels have also been reported in aquatic plant species such as Phragmites australis (Pietrini et al, 2003). Alterations in NADPH levels have been reported in plants exposed to heat, chilling and other abiotic stresses (Schrader et al, 2004(Schrader et al, , 2007.…”
Section: Acknowledgmentsmentioning
confidence: 91%
“…ex Steudel was associated with a large pool of GSH, protecting the activity of many photosynthetic enzymes against the thiophilic bursting of Cd exerting a direct important protective role in the presence of Cd. 119 Cai et al 120 reported that exogenously applied GSH significantly increased chlorophyll content, net photosynthetic rate, maximal photochemical efficiency of PSII (Fv/Fm) and effective PSII quantum yield Y(II) in Cd exposed plants. Further, GSH addition significantly increased root GSH content in plants under Cd exposure and induced upregulation in PCs Bing 97252 (Cd tolerant) throughout than Xiushui63 (Cd sensitive).…”
Section: Resultsmentioning
confidence: 99%
“…Increased concentration of GSH has been observed with the increasing Cd concentration in various plants. [119][120][121][122][123][124] …”
Section: Resultsmentioning
confidence: 99%
“…Detoxification of heavy metals, especially non-essential heavy metals, is often attributed to post-translationally synthesized thiol-rich short metal binding proteins termed phytochelatins (Grill et al 1985). The accumulation (Zacchini et al 2009) and binding (Iori et al 2012) of metals, as well as the protection of the integrity and functionality of physiological , Pietrini et al 2010, Fernàndez et al 2012) and metabolic processes (Pietrini et al 2003, Di Baccio et al 2010, might result by a restricted uptake and/or limited root-toshoot translocation. The metal might be recovered in the aerial parts (Castiglione et al 2007).…”
Section: Response Of Salicaceae To Pollutants and Monitoring Of The Cmentioning
confidence: 99%